2012
DOI: 10.15376/biores.8.1.231-237
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bending Properties for Turkish Red Pine (Pinus brutia Ten.) Lumber using Stress Wave Method

Abstract: Bending properties of Turkish red pine (Pinus brutia Ten.) lumber pieces were predicted using the stress wave method. The lumber samples were taken from 30-to 80-year-old red pine trees harvested from a southwest site in Turkey. MTG timber grader was utilized to predict modulus of elasticity (MOE) and modulus of rupture (MOR) values of lumbers with 40 mm x 90 mm in cross section and 3 meters in length. Static MOE and MOR values of the lumber pieces were determined using a three-point bending test. The coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 8 publications
4
22
0
Order By: Relevance
“…They have reported a coefficient of determination of 0,84 for bending stiffness. Similar coefficient of determination value has been reported by Guntekin et al (2013) for bending stiffness of Turkish Red pine.…”
Section: Resultssupporting
confidence: 88%
“…They have reported a coefficient of determination of 0,84 for bending stiffness. Similar coefficient of determination value has been reported by Guntekin et al (2013) for bending stiffness of Turkish Red pine.…”
Section: Resultssupporting
confidence: 88%
“…MOE dyn shows significant correlation with compressive MOE (R = 0.92), R hardness (R = 0.85), T hardness (R = 0.77), and tensile stress at maximum load (R = 0.73) ( Table 3). Regression analysis reveals a linear relationship between MOE dyn and MOE static with R 2 of 0.77 (Figure 1), which is consistent with those reported by Horvath et al 2010 (R 2 = 0.78) and Guntekin et al 2013 (R 2 = 0.84). This study gives evidence that stress wave velocity obtained by the instrument Treesonic Microsecond Timer (TMT, Fakopp) is suitable to make reliable prediction of bending, compressive, hardness and tensile strength properties of the most commonly used timber species of the region, in the field.…”
Section: Relation Among Dynamic Moe and Mechanical Propertiessupporting
confidence: 87%
“…For instance, Li et al [18] presented the stress wave velocity model to diagnosis the internal defects in urban trees. According to Guntekin et al [19], the imaging results and detection precision still need to be improved, although many stress wave detection devices are capable of generating twodimensional or three-dimensional tomographic images of wood cross sections. Sun and Wang [20] found that the twodimensional image detected by the stress wave was not accurate enough to show the shape of the decayed area.…”
Section: Introductionmentioning
confidence: 99%